O que busca uma alma inquieta? - Corso, Maria das Graças Ramos Del (2011)
This work results from clinical experiences with children diagnosed with psychopathological problems. Looking at the different diagnostic configurations, often undefined, and at the therapeutic recommendations, the investigation intended to go beyond the field of symptomatology. The goal at play was to think about the framework where the phenomena that are usually taken as proofs of the psychopathology constitute mere signs of an invisible reality , which manifests itself through behaviors such as non-stop movements , never being quiet , doing for the sake of doing , that is, actions always accompanied by excesses, and by a lack of thinking . The work proposes the necessity of understanding at the service of what these phenomena occur, and of their implications. Based on psychoanalysis articulated the fundamental psychopathology, the work indicates the need of reading an uneasy state not only in its content e.g. as signified, but mainly as a signifier that has to be addressed case by case